WHAT GRADUATE SCHOOL DIDN'T TEACH YOU ABOUT INSTRUCTIONAL DESIGN CONSULTING. Issue 9 (6th December 2021) - Gardner, Joel L.; Snyder, Dawn; Guilkey, Jim; Abbott, Virginia; Barclay, Matt
Abstract: Instructional design consultants provide learning and performance solutions for their clients. However, it can be difficult for instructional design students and newly graduated instructional designers to adapt to the realities of consulting in a real‐world context. This difficulty is magnified by significant technological, social, and other disruptions that often occur in work and learning environments. In our observation, newly graduated instructional design consultants enter the workforce equipped with powerful tools, theories, and models for increasing learning but are less equipped to consult with their clients and other stakeholders. This article is based on our experiences as instructional design consultants, and we share key practice‐based, expert‐informed skills, principles, and strategies for success as an instructional design consultant. We then share strategies that can be used to overcome consulting constraints and obstacles. We share ways to maintain fidelity to principles amidst disruptions and outline strategies for ensuring that learning and performance solutions have long‐term resilience and impact. We conclude with reflections on the education and practice of instructional design consulting.